Potensi Pelanggaran Hak Cipta dalam Pembuatan Karya Buku dengan Menggunakan Bantuan Aplikasi ChatGPT Berdasarkan Undang-Undang Nomor 28 Tahun 2014 tentang Hak Cipta - Sri Maharani M.T.V.M; Shefina Ja Ashari (Jurnal Hukum Lex Generalis, 2025)
Artificial Intelligence such as ChatGPT has a significant impact on the creative writing process, including book works. This study aims to analyze the potential for plagiarism in book works produced with the assistance of the ChatGPT application based on Copyright Law, considering the limitations of ChatGPT usage, and to formulate preventive and repressive measures for creators in addressing such risks. The research method used is normative legal analysis. The creation of books using ChatGPT may infringe on copyright or constitute plagiarism if it lacks originality. Creators can address the potential for plagiarism by implementing repressive and preventive measures.